Multicarrier delay diversity modulation for MIMO systems. - Jun Tan (IEEE Transactions on wireless communications)
Multicarrier delay diversity modulation (MDDM) is a scheme that uses orthogonal frequency division multiplexing (OFDM) on a "multipath" channel that is generated by using delay diversity. The full diversity criterion for MDDM is proven and illustrative examples of full-diversity codes are obtained based on the established criterion. Coding gains and interleaver designs are also considered and analyzed. Simulation results for MDDM on quasi-static flat and frequency-selective fading channels are discussed. MDDM is established as a strong competitive technique to existing space-time block codes and space-time tellis codes techniques for multiple input multiple output systems.